Burnout syndrome in dental surgeons from Lima Metropolitan hospitals - Robles Velásquez, Ronald (2010)
This research was carried out in a probabilistic randomized sample of 117 dental surgeons who work in hospitals from the Armed Forces, Social Security and the Ministry of Health (MINSA) from Lima and El Callao, during the months of March and April 2008. Its objective was to determine the levels of the Burnout Syndrome in this population and its association with some socio-demographic, labor and general health variables. The Maslash Burnout Inventory questionnaire, as well as a personal data sheet were applied for such study. The results show that 44.6 % of the dental surgeons present severe-level Burnout Syndrome and statistically significant associations were found with sex and the presence of health problems as variables.